Managerial Strategy of Female Health Workers Plays A Dual Role (Swot Analysis at Wira Bhakti Clinic in Lhokseumawe City) - Verra Rahwany; Purwadhi Purwadhi; Mira Veranita (CV. Civiliza Publishing, 2026)
This study aims to formulate a managerial strategy for female health workers to play a dual role at the Wira Bhakti Clinic in Lhokseumawe City through a SWOT analysis approach. This study uses a qualitative descriptive design with a case study approach. The research subjects were selected using purposive sampling techniques totaling 10 health workers (doctors, nurses, midwives) who had the status of active soldiers' wives. Data collection was carried out through in-depth interviews, observations, and documentation, which were then analyzed using the Miles & Huberman interactive model and SWOT matrix (IFAS and EFAS). The results of the study show that the dynamics of dual roles at Wira Bhakti Clinic run through a hierarchical mechanism, where wives with the rank of Enlisted tend to support the clinical operational burden to cover the vacancies left by wives with the rank of Officer or Non-Commissioned Officer who have high obligations in the Persit organization. Based on the SWOT analysis, the main strength lies in the husband's support and financial stability, while the main weakness is the time conflict due to the organization's mandatory activities. This study recommends a